2017
DOI: 10.1163/22244662-06301003
|View full text |Cite
|
Sign up to set email alerts
|

The status and distribution of Gazella gazella (Artiodactyla: Mammalia), and other mammals of the Hatay province in southern Turkey

Abstract: Gazella gazellawas discovered recently in a restricted area in the Hatay province, Southern Turkey, which constitutes the northern most point of the distribution of this species in the world. To determine the distribution of the population of mountain gazelles in the Hatay region, 17 camera-traps were set along 45 km, on a line from the south to north along the Syrian border. The traps were in the field for about five months from late May to mid-October in 2016. Field observations and conversations with local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The gray wolf ( Canis lupus ) is one of the most common predator species (6,000–8,000 individuals: Ambarli, Ertürk & Soyumert, 2016) occupying Anatolia (Asian part of Turkey), Turkey. It inhabits almost all type of habitats, ranging from deciduous Black sea forests to open steppes of middle and semi-deserts of south-eastern Anatolia (Ambarli, Ertürk & Soyumert, 2016; Çoğal & Sözen, 2017). As an apex predator, the wolf plays a crucial role in the ecosystems by regulating large ungulate and meso-predator numbers (Ripple et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The gray wolf ( Canis lupus ) is one of the most common predator species (6,000–8,000 individuals: Ambarli, Ertürk & Soyumert, 2016) occupying Anatolia (Asian part of Turkey), Turkey. It inhabits almost all type of habitats, ranging from deciduous Black sea forests to open steppes of middle and semi-deserts of south-eastern Anatolia (Ambarli, Ertürk & Soyumert, 2016; Çoğal & Sözen, 2017). As an apex predator, the wolf plays a crucial role in the ecosystems by regulating large ungulate and meso-predator numbers (Ripple et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The study site has a rich mammal community, as 23 mammal species were recorded in this area, including Canis aureus (golden jackal), Canis lupus (wolf) and Vulpes vulpes (red fox), which are classified as natural predators of mountain gazelle, and some others such as Hyaena hyaena (striped hyena), Felis chaus (jungle cat), Felis silvestris (wildcat), Hystrix indica (Indian porcupine), Lepus europaeus (wild rabbit) and Meles meles (European badger) (Akay et al., 2011 ; Çoğal & Sözen, 2017 ). In the study area, domestic sheep herds are also frequently observed throughout the year.…”
Section: Methodsmentioning
confidence: 99%
“…At the microenvironmental level, gazelle populations are faced with predation risk, species-specific infections, parasite infestations, and cohabitation and competition with domestic livestock. Despite some studies on genetics ( 4 , 17 ), parasite infestation ( 18 , 19 ), population status and distribution ( 20 ), and appropriate conservation planning ( 21 ), mountain gazelles are attractive and endangered mammal species and remain one of the least studied species in Türkiye. Therefore, studies addressing metabolic, endocrine and reproductive characteristics are essential to ensure the survival of this species in Türkiye.…”
Section: Introductionmentioning
confidence: 99%